Introduzione a Poesia e psicoanalisi. L’altra contemporaneità (ENTHYMEMA, 2019)
Introduction to the special section Poetry and Psychoanalysis. The Other Contemporaneity, edited by Matteo Bonazzi, Francesco Adriano Clerici, Rosalba Maletta.
Keywords: poetry; psychoanalsys